Grid technologies for E-Health - Kldiashvili, Ekaterina (Hershey Medical Information Science Reference, 2011)
"This book presents applications of the possibilities of Grid technologies for telemedicine and eHealth as well as presentation of ongoing projects and achievements"--Provided by publisher.
Keywords: Medical telematics; Telecommunication in medicine; Computational grids (Computer systems)